Protein supplementation does not improve aerobic and anaerobic fitness in collegiate dancers performing cycling based high intensity interval training - Alfiero, C. J.; Brooks, S. J.; Bideganeta, H. M.; Contreras, C.; Brown, A. F. (Journal of Dance Medicine & Science, 2021)
The effects of a 6-week cycling high-intensity interval training (HUT) concurrently with protein supplementation on aerobic and anaerobic fitness and body composition in collegiate dancers was investigated. Eighteen participants enrolled in a collegiate dance program were matched into three groups: high-protein (HP; 90 g·d-1), moderate-protein (MP; 40 g·d-1), and control (C; 0 g·d-1). All participants performed a 6-week HUT intervention. Participants completed a graded exercise test, Wingate anaerobic test (Wingate), and dual energy x-ray absorptiometry scan before and after the intervention. Peak heart rate (HRpeak), peak oxygen uptake (VOpeak), peak power output (PPO), lactate threshold (LT), and ventilatory thresholds 1 (VT1) and 2 (VT2) were assessed during the graded exercise test. Peak power output, mean power output (MPO), and fatigue index (FI) were assessed during the Wingate. Lean mass (LM), fat mass (FM), visceral adipose tissue, appendicular skeletal muscle mass, and appendicular skeletal muscle mass index were assessed during dual energy x-ray absorptiometry. Body composition index (BCI) was calculated from pre and post LM and FM. Habitual diet was recorded weekly. Significance was set at p < 0.05. No significant differences in VO2peak and percent fat mass (%FM) were observed between groups prior to the intervention. Significant main effects for time were observed for HRpeak (p = 0.02), VO2peak (P < 0.001), PPO (p < 0.01), LT (p < 0.001), VT1 (p < 0.001), and VT2 (p < 0.001) during the graded exercise test, and PPO (p < 0.01) and FI (p < 0.01) during the Wingate. Significant main effects for time were observed for LM (kg; p = 0.01) and FM (kg; p < 0.01). Body composition index was improved for all groups, however, no significant differences by group were observed. No significant differences were observed between groups for the measured outcomes (p > 0.05). Therefore, there was no effect of protein supplementation in the short 6-week intervention. This cycling based HUT routine increased physical fitness, optimized aesthetics, and was a simple addition to an existing collegiate dance curriculum.